Larangan Allah Atas Perselingkuhan Implementasi Maleakhi 2 : 14 - 16 terhadap Keluarga Kristen Masa Kini - Herdiana Sihombing; Jefri Ade Nasution; Widia Idola Novita Hutabarat (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study discusses God’s prohibition of adultery as stated in Malachi 2:14–16 and its relevance to contemporary Christian families. Adultery is regarded as a betrayal that not only damages the marital relationship but also violates the sacred covenant with God. The study highlights that an ideal Christian family is one founded on God’s Word, upholding love, faithfulness, and a life of reverence to God. However, in reality, many families face challenges such as individualistic lifestyles, the negative impact of social media, poor communication, and declining spiritual values. Real-life cases, including infidelity leading to violence, reveal the urgency of applying biblical principles to build strong families. Thus, Malachi 2:14–16 serves as a theological foundation affirming the importance of faithfulness and love in preserving the integrity of Christian marriage. Furthermore, poor communication, a lack of mutual understanding, and declining spiritual engagement can strain relationships, making it more difficult to maintain a strong, healthy marriage. These challenges highlight the critical need for Christian families to return to the foundational principles outlined in God’s Word, including the importance of sacrificial love, trust, and mutual respect. The study draws attention to the practical implications of these teachings, urging families to actively engage in spiritual practices, open communication, and mutual support to overcome the pressures of modern life. By doing so, they can create environments where love and faithfulness flourish, ensuring that their relationships remain strong and rooted in the divine covenant established by God. Thus, Malachi 2:14-16 remains highly relevant today as a timeless reminder of the sacred nature of marriage and the importance of nurturing healthy, God-centered relationships in Christian families.